A modern history of European cities. 1815 to the present. - Wakeman, Rosemary (Bloomsbury Academic, 2020)
This original survey text comprehensively explores modern European urban history from 1815 to the present day. It provides a journey to cities and towns across the continent, in search of the patterns of development that have shaped the urban landscape as indelibly European. The focus is on the built environment, the social and cultural transformations that mark the patterns of continuity and change, and the transition to modern urban society. Including over 60 images that serve to illuminate the analysis, the book examines the questions: is there a European city, and if so, what are its characteristics? The author offers an interdisciplinary approach that incorporates concepts from cultural and postcolonial studies, as well as urban geography, and provides full coverage of urban culture and society not only in Western Europe, but also in Eastern and Southern Europe, using various cities and city types to inform the discussion. The book also provides hitherto neglected detailed coverage of European urbanization post-1945 which allows us to more clearly understand the modernizing arc the region has followed over the last two centuries
Keywords: Stadtgeschichte; Städtebaugeschichte; Stadtgestalt; Stadtentwicklungsforschung; Stadtplanung; Städtebauliches Leitbild; Geschichte; Stadtgesellschaft; Sozialwandel; Urbanistik; Urbanismus; Moderne; Europäische Stadt